Individual Capability, Individual Motivation, Leadership, Organizational Climate, Workgroup Effectiveness to Performance (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to empirically examine the effect of human capital on employee performance. The sample in this study amounted to 50 respondents in the small and medium enterprises. The data used are primary data obtained by distributing questionnaires directly with the simple random sampling technique. The influence test model used is multiple linear regression, analyzed using SPSS 22.0. The results in this study indicate that together all variables of human capital: individual capability, individual motivation, leadership, organizational climate and work group effectiveness have a significant positive effect on employee performance. Partially Individual motivation has a positive effect on performance, organizational climate has a positive effect on performance, and work group effectiveness has a positive effect on performance. Individual capability has a negative effect on performance and leadership no significant effect on performance. The variable used in this study can explain 48,3% of employee performance, based on the acquisition of the coefficient of determination () that is equal to 0,483.